Distribution of Wolbachia infection in butterflies (Lepidoptera): First systematic report from Thailand - Panukorn Boonsit; Itsanun Wiwatanaratanabutr; Perran A. Ross; Frédéric Grandjean; Chris Austin; Somsak Kramchote (Oriental Insects, 2023)
Wolbachia is a genus of Rickettsia-like bacteria that infects a broad range of insect species throughout the world. It often influences host reproduction to facilitate its transmission to their offspring and spread through populations. The occurrence and ecology of Wolbachia has not been surveyed in detail in Thai butterflies. In this study, we conduct the first systematic survey of Wolbachia infection by sampling 623 specimens from 46 butterfly species from 5 families obtained from tropical forests in 3 geographic regions of Thailand. Wolbachia infections were detected using three PCR primer sets: 16S rRNA, ftsZ and wsp. The results showed evidence for widespread Wolbachia infection in Thai butterflies. The Wolbachia presence was confirmed in 291 individuals from 17 butterfly species of 2 families, comprising 86 individuals from the Central Region (32 males and 54 females), 72 individuals from the Northeast Region (25 males and 47 females), and 133 individuals from the West Region (46 males and 87 females). This report will be useful for understanding the distribution of Wolbachia in butterflies from Thailand.
Keywords: Insect symbiosis and bacterial influences; Insect and Arachnid Ecology and Behavior; Insect-Plant Interactions and Control